Cardiac cine MR-imaging at 3T: FLASH vs SSFP. - Tyler, D; Hudsmith, L; Petersen, SE; Francis, J; Weale, P; Neubauer, S; Clarke, K; Robson, M (2006)
The implications of an increase in field strength, from 1.5 T to 3 T, for routine functional cardiac examinations have been systematically investigated. Flip angle optimization was carried out for identical SSFP and FLASH cine imaging sequences at 1.5 T and 3 T, which supported the use of 20 degrees (FLASH 1.5 T and 3 T) and >60 degrees (SSFP 1.5 T and 3 T). The optimized sequences were applied in a study of cardiac function in a group of ten normal volunteers. Both SSFP and FLASH sequences showed significant SNR increases in the myocardium and blood at 3 T compared with 1.5 T, increases of 48% and 30% (myocardium and blood, respectively) for the SSFP sequence and 19% and 13% for the FLASH sequence. The SSFP sequence also showed a significant increase in CNR (22%). Image quality assessment revealed that the SSFP acquisitions were superior to FLASH at both field strengths. Although SSFP contained more artifacts at 3 T, they would not prevent its clinical use. We conclude that cardiac functional examinations at 3 T should use SSFP sequences.